Evaluation of the Use of Canva Media in Learning to Write Anecdotal Texts: A Literature Study - Sasmita, Cahya (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This article aims to assess the use of Canva media as a medium in learning to write anecdote texts. This study was conducted through a literature study of a number of literatures relevant to the topic of using learning media, Canva media, and anecdote text writing skills in the context of Indonesian language learning. Writing anecdote text is a language skill that requires creativity and interesting presentation skills, so it requires learning media that is not only oriented towards delivering material, but also stimulating ideas and student involvement. Through the use of Canva media, teachers can facilitate a more visual, interactive and structured learning process. The results of this study are expected to show that the use of Canva media can increase students’ learning motivation, facilitate the preparation of story outlines, and provide an overview of the potential of graphic design technology in supporting writing learning.